Catheter pulmonary vein isolation with drug testing of dormant conduction and detection of non-pulmonary vein triggers and high frequency stimulation of left atrial ganglionated plexi in patients with paroxysmal atrial fibrillation - Yu. S. Krivosheev; D. I. Bashta; A. A. Simonyan; N. A. Tihonova; K. V. Modnikov; T. A. Myznikova; Z. A. Mishodzheva; V. N. Kolesnikov (Патология кровообращения и кардиохирургия, 2018)
Background. Catheter pulmonary vein isolation (PVI) is the main interventional procedure for treatment of atrial fibrillation (AF). Recurrences of arrhythmia paroxysms in the postoperative period are mainly determined by reconnection of conduction from the pulmonary veins. However, non-pulmonary vein triggers and a positive vagal response of ganglionated plexi (GP) to high frequency stimulation after PVI confirmed by drug testing may affect the long-term efficacy of catheter AF ablation. Aim. To evaluate the efficacy of PVI isolation after drug testing and a negative response to high-frequency stimulation and a positive response to high-frequency stimulation but without subsequent ablation in patients with paroxysmal AF, as well as the efficacy of PVI confirmed by drug testing in patients having nonpulmonary vein triggers. Methods. The present analysis is a part of the randomized study on the comparison of PVI confirmed by drug testing with the absence of non-pulmonary vein triggers and a positive response of GP to high-frequency stimulation with and without GP ablation. PVI was performed in 311 patients. Ninety-six patients were excluded because they required additional GP ablation. Two hundred and fourteen patients were divided into three groups: PVI with a positive GP response (posGP) to high-frequency stimulation without GP ablation (group I, n = 97), PVI with a negative GP response (negGP) to high-frequency stimulation (group II, n = 79) and PVI with non-pulmonary vein triggers (group III, n = 38). The primary endpoint of the study was the freedom from any atrial tachyarrhythmias after 12 months of follow-up confirmed by 24-hour Holter monitoring. The secondary endpoints included the frequency of detecting dormant pulmonary vein conduction, non-pulmonary vein triggers, negative GP response to high-frequency stimulation after catheter PVI. The patients were followed 3, 6, 9, 12 months after the ablation procedure. Results. At the end of the follow-up 57 (72.2%) patients in the PVI + negGP group (group II), 58 (59.8%) patients in the PVI + posGP group (group I) and 20 (52.6%) patients in the PVI + NPT (group III) were free from any atrial tachyarrhythmia (р=0.07; log-rank test). A statistical significance in the efficacy was observed when group II was compared with group III (72.2% and 52.6%, р = 0.028, log-rank test). In the course of primary ablation following PVI, when performing drug testing, dormant atriovenous conduction sites were observed in 105 (33.8%) patients, while non-pulmonary vein triggers (n = 79) were recorded in 38 (12.2%) patients. The frequency of negative GP responses to high-frequency stimulation after PVI accounted for 28.3%. Conclusion. Pulmonary vein isolation confirmed by drug testing, without a response of GP to high-frequency stimulation tends to provide higher efficacy in maintaining the sinus rhythm as compared with PVI and a positive GP response to high-frequency stimulation, but without a statistical significance, whereas nonpulmonary vein triggers after PVI are associated with lower efficacy in the long-term follow-up.